(untitled) (Canadian Journal of Emergency Management, 2022)
With Canada now halfway through its third year of the COVID-19 pandemic, while concurrently facing various climate change related threats across the country throughout all seasons of the year, the emergency management domain continues to gain importance both in practical and academic terms.